Freshening, stratification and deep-water formation in the Nordic Seas during marine isotope stage 11. (15th November 2021) - Doherty, John M.; Ling, Yuet F.; Not, Christelle; Erler, Dirk; Bauch, Henning A.; Paytan, Adina; Thibodeau, Benoit
Abstract: The Atlantic meridional overturning circulation (AMOC) is a critical element of Earth's climate system and it is currently weakening. While this weakening is frequently explained by freshwater-driven disruptions to deep-water formation, uncertainties about the impacts of prolonged freshening limit our capacity to predict its future state. For example, during the warm and unusually long marine isotope stage (MIS) 11 interglacial, ∼424 to 374 ka, several lines of evidence suggest that a strong AMOC persisted concomitant with fresher-than-present conditions in the Nordic Seas, challenging our current understanding of deep-water formation. Here, we present new foraminifer-bound nitrogen isotope data along with multiple additional geochemical reconstructions of upper-ocean hydrography in the Nordic Seas during this anomalous interval. Our data suggest that a weak summer stratification was driven by the prolonged upper-ocean accumulation of freshwater beginning at the onset of the climatic optimum, ∼410 to 407 ka, which could have helped precondition the region for deep-water formation. A box model constrained by paleo-proxy data additionally suggests that the density gradient between the subpolar North Atlantic and Nordic Seas was favorable for the onset of deep-water formation in the Nordic Seas during the climatic optimum. It is thus likely that the Nordic Seas became a locus of deep-water formation around this time. Enhanced northern-hemisphere heating driven by deep-water formation in the Nordic Seas may have been important for delaying glacial conditions, thereby driving the extended warming characteristic of MIS 11. Such findings may also be relevant for near-future changes under a relatively fresher high-latitude North Atlantic. Highlights: Hydrography and convection reconstructed in the Nordic Seas during MIS 11. Active convection in the Nordic Seas occurred during prolonged freshwater input. Freshwater input does not always impede convection on interglacial timescales. Onset of polar convection may have helped to sustain interglacial conditions.